Enhancing stationkeeping and motion reduction of floating offshore wind turbines using wave devouring propulsion technology - Jingru, Xing (Cranfield University, 2024)
This PhD thesis investigates the enhancement of stationkeeping and motion reduction in Floating Offshore Wind Turbine (FOWT) platforms through the application of biomimeticinspired Wave Devouring Propulsion (WDP) technology. Through a multidisciplinary approach that encompasses a comprehensive literature review, numerical simulations, and scaled-down water tank experiments, this research confirms the potential of WDP technology to significantly improve the stationkeeping capabilities of FOWT platforms. The thesis is structured around four key objectives, each addressing a critical aspect of WDP application in FOWT platforms—from theoretical underpinnings and simulation tool development for Fluid-Structure Interaction (FSI) analyses, to the investigation of sub-structure dynamics and practical feasibility studies for the integration of innovative sub-structures aimed at stationkeeping. This thesis contributes to the field by providing a comprehensive overview of WDP technology, introducing a novel numerical model for FSI simulations, insights into the hydrodynamic performance of submerged hydrofoils, and the experimental verification of WDP technology’s effectiveness in enhancing platform stationkeeping. Notably, the study proposes optimized design guidelines for foil implementation, demonstrating a significant reduction in mooring tension and thereby advancing the practical applicability of WDP in the marine industry. By advancing the understanding and application of WDP technology, this thesis lays the groundwork for significant improvements in the sustainability and efficiency of maritime operations, aligning with global efforts towards achieving net-zero emissions in the maritime sector.
Liyun, Lao - Associate Supervisor
Keywords: Flapping foil; Marine environment; Computational Fluid Dynamics (CFD); Fluid-Structure Interaction (FSI); Platform stabilisation.; underpinnings